On the boundary value problem with integral conditions for the systems of differential equations of second order - Kvedaras, B. (Lithuanian Mathematical Journal, 1967)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Кведарас. О краевой задаче с интегральными условиями обыкновенных дифференциальных уравненийB. Kvedaras. Apie kraštinį uždavinį su integralinėmis sąlygomis antros eilės diferencialinių lygčių sistemoms